A Conceptual Study on the Effects of Bullying on Academic Engagement among Elementary School Students - Setiawan, Anisha Putri; Assakdiah, Annisa; Fathonah, Dewi Nur; Prabowo, Yoga Dwi; Rozzaqyah, Fadhlina (Program Studi Bimbingan dan Konseling, Fakultas Ilmu Pendidikan, Universitas Negeri Medan, 2024)
This study provides a theoretical investigation into the multidimensional impacts of bullying on students’ academic and social activities within elementary schools. Utilizing a literature review approach, this paper synthesizes findings from academic journals, educational reports, and media publications to explore how bullying affects students’ learning engagement, classroom participation, and mental well-being. Documentation methods were employed to collect and analyze relevant sources, enabling a conceptual understanding of bullying as one of the major ethical and psychological challenges in education. The findings reveal that victims of bullying often experience decreased academic performance, emotional distress, and social withdrawal due to persistent fear and anxiety in school environments. This study contributes to the theoretical and practical discourse on creating safe learning environments and highlights the necessity of preventive and intervention strategies to promote anti-bullying awareness among educators and policymakers.